Penilaian Dan Pengukuran Hasil Belajar Pada Peserta Didik Berbasis Analisis Psikologi - Yunita Eka Nur Prastiwi; Arba'iyah; Afifah Amatullah Al Barru; Achmad Syarif Hidayatullah (LPPM Politeknik Pratama, 2023)
In the learning process, of course, not far from one important aspect, usually called assessment. to find out students' progress. Good learning quality can be seen in a good learning system. This can be seen in the final results or assessment. In general, this research is used to discover the basic concepts, the role of psychology in the assessment and measurement of learning outcomes, and forms of cognitive assessment in the Assessment and Measurement of Learning Outcomes in Students Based on Psychological Analysis. The method used in this research is Library Research, which collects data sources or written information from books, articles, or other written sources relevant to this study's discussion. The results of this study are that the factors that influence learning outcomes consist of two, namely internal and external. In addition, this study explains the functions and tools of assessment, the role of psychology in evaluation, and forms of cognitive appraisal in assessing and measuring student learning outcomes.